Strengthening the Capacity of Healthcare Providers through the Introduction of Hematological Indices as Sepsis Markers - Benny Hartono; Yeti Indrawati (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Sepsis is the most common cause of increased mortality and morbidity. Culture is a gold standard, but it is time-consuming and has a low positive rate. Currently, procalcitonin is a reliable biomarker for diagnosing and predicting sepsis, but the cost is high, and it is not always available in every laboratory facility. Objective: To examine neutrophil-lymphocyte count ratio(NLCR), platelet distribution width(PDW), and Mean Platelet Volume(MPV), which can be used as markers of sepsis compared with Procalcitonin(PCT). Method: This was a cross-sectional study of 40 adult patients who entered the Emergency Department. The study took place from May 2017 to June 2017. All patients had blood samples taken on the first day of treatment. Blood culture is used as the gold standard. PCT, NLRC, PDW, and MPV values were compared between patients with positive and negative blood cultures. Results: of 40 adult patients, 25 had positive blood culture, and 15 had negative results. The performance of PCT, NLRC, PDW, and MPV was significantly higher in patients with positive blood culture compared with the negative consequence AUC=0.915/0.768/0.756/0.733, P=<0.001/0.005/0.012/0.007,respectively).NLCR was found to have a better diagnostic efficiency for predicting sepsis, with greater sensitivity and accuracy than platelet indices. Spearman correlation test showed a significant correlation between NLCR and PCT levels in sepsis patients (rs=0.504; P=0.001). The combination of NLCR, PDW, and MPV demonstrated a good diagnostic performance (sensitivity 76%, specificity 66,7%), similar to procalcitonin (sensitivity 88%, specificity 66,7%). Conclusion: The increase of NLCR has an opportunity to be an indirect marker of increased PCT levels. Combining these three parameters could be a marker to distinguish sepsis from non-sepsis.